Curriculum Integration Constructs in Integrated Islamic Elementary School - Basri, Hasan; Abdullah, Alamin (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
Despite the extensive documentation of educational curriculum research, there is still a lack of studies examining the constructs of integrated curriculum and its presentation by incorporating religious content into various subjects. To address this gap, this research aims to analyze the constructs of integrated curriculum in terms of curriculum content, presentation, and the supporting factors for implementation in the learning process. Data collection involves document analysis of curriculum guidelines, teacher manuals, student package books, and direct observation of learning implementation. The study's findings, based on document analysis and observation, are further reinforced through interviews with the school principal and teachers. The research reveals that the curriculum constructs at SDIT Insantama Kendari encompass the classification of material comprising elements of Islamic character formation, introduction to Islamic culture (tsaqafah), and the introduction of science and skills. These components are presented in the learning activities by integrating religious education into all subjects through team teaching, non-co-education, and a shared perception among teachers who assume the role of religious educators.